COVID-19-induced concerns and graduate students’ motivation for programme completion in a Nigerian university (2023)
This study examined the impact of COVID-19-induced concerns regarding health, finance and learning on graduate students’ motivation for programme completion in Nigeria. A quantitative research method using survey approach was adopted for the study. The study utilized an online survey to gather data from 1846 graduate students from a purposively selected university in Nigeria. A model was proposed to serve as a framework for the analysis of the data collected. The model consisted of four constructs: health concerns, financial concerns, learning concerns and motivation for programme completion. A Partial Least Square- Structural Equation Modeling (PLS-SEM) technique in WarpPLS 7.0 was used for data analysis. Results revealed amongst others that the COVID-19-induced health concerns positively and significantly impacted graduate students’ motivation for programme completion. Additionally, the financial concerns related to the pandemic had a negative significant impact on graduate students’ motivation for programme completion. Further, the study found that COVID-19-induced concerns regarding health influenced graduate students’ concerns regarding finance. Similarly, COVID-19-induced concerns regarding finance significantly influenced graduate students’ learning concerns. Hence, the study suggested that university administrators and other stakeholders should assist graduate students with various forms of financial empowerment schemes, student loans and scholarships that could cushion the effect of the financial fallout of the pandemic on the graduate students and mitigate against possible dropout of the graduate students from graduate studies